Indonesia-Australia Comprehensive Economic Partnership Agreement: Building the Powerhouse - Arianto Patunru; Andree Surianta; Pingkan Audrine (Center for Indonesian Policy Studies (CIPS), 2021)
After almost a decade of negotiations, the Indonesia-Australia Comprehensive Partnership Agreement finally came into force in July 2020. Under the current global economic condition, and particularly with the global trade disruption caused by the COVID-19 pandemic, the IA-CEPA partnership came at an appropriate time. The IA-CEPA opens up two opportunities for Indonesia and Australia, allowing them to focus on their complementarities at a more disaggregated level and ensuring that cooperation is not limited to trade and investment, and domestic reforms. Trade in the food and beverage manufacturing sector, and investment in higher education, are the two areas at the core of IA-CEPA. To address critical issues and challenges in those areas, this policy paper proposes four recommendations for consideration.
Keywords: 330; IA CEPA; Indonesia; Australia; international trade agreement